AB0046 Metabolism and osteoarthritis are linked by adipokines. (15th June 2017) - Hülser, M-L; Schreiyäck, C; Luo, Y; Bozec, A; Schett, G; Neumann, E; Müller-Ladner, U
Abstract : Background: Obesity and hyperinsulinemia are of increasing importance in the Western society. Both obesity and insulin resistance lead to changes in expression of adipokines such as adiponectin, visfatin or leptin, which appear to be immunomodulatory factors also in rheumatic diseases. Objectives: Since osteoarthritis (OA) is often accompanied by hyperinsulinemia and obesity, we combined both mouse models (destabilization of the medial meniscus (DMM) and high-fat diet (HFD)). Here, we evaluated and correlated the systemic and local effects of both models at different states of OA development with special focus on the local/systemic expression of the adipokines adiponectin, visfatin and leptin over time. Methods: HFD (mainly consisting of saturated fatty acids) to induce obesity and hyperinsulinemia, and ND (normal diet) as control were fed to C57Bl/6 mice for 3 months followed by surgical OA induction (time point 0). Tissues and sera were collected at different time points after DMM-mediated OA induction (4, 6, 8 weeks). Adipocytokine (leptin, visfatin, adiponectin and IL-6) serum levels were measured by ELISA. Histological stainings of the joints (H/E, safranin O, pappenheim and Masson-Goldner's trichrome) were evaluated and arthritis progress was scored. Immunohistochemical stainings of the joints were performed to evaluate the local distribution of adipokines, which were correlated to systemic adipocytokine levels and the respective arthritis score. Results: Low systemic IL-6 levels confirmed that no acute inflammation due to surgery or infection was present in all animals. OA induction was visible at all time points, which was aggravated in HFD compared to ND mice (OA score: 4 weeks ND 0.87 vs. HFD 0.93, 6 weeks ND 1.44 vs. HFD 3.69, 8 weeks ND 1.78 vs. HFD 2.18). Systemic levels of leptin were significantly induced by HFD confirming the induction of insulin resistance, but DMM decreased leptin levels at all time points (significantly for 3 out of 6 groups, e.g. 4 weeks: HFD healthy vs. HFD DMM 18.4 ng/ml vs. 3.7 ng/ml). Interestingly, the systemic increase of adiponectin by DMM was time dependent (only 8 weeks after surgery: HFD healthy vs. HFD DMM 5176 ng/ml vs. 6149 ng/ml) but independent of diet. However, HFD in combination with DMM did not show significant effects on systemic levels of adiponectin, visfatin or IL-6. Conclusions: HFD deteriorates OA in the DMM model. Systemic leptin levels were elevated by HFD/insulin resistance but reduced by DMM, which could not be observed for the mainly proinflammatory adipokine visfatin. Of note, systemic inflammation as shown by systemic IL-6 levels was low in all animals. The stage of OA development influences adiponectin levels, which were only increased systemically 8 weeks after surgery. In summary, systemic levels of adipokines are altered by DMM and HFD as well as the combination of both models and the analyzed adipokines show differing reactions to these factors. Disclosure of Interest: None declared